2022
DOI: 10.18502/jmehm.v15i7.11049
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the recurrence of medical errors in hospitals and the preventive strategies: a scoping review

Abstract: Due to the high value of human life, the occurrence of even one error that leads to death or complications is of great consequence and requires serious attention. Although significant efforts have been made to ensure patient safety, serious medical errors continue to exist. This study aimed to identify the factors associated with the recurrence of medical errors and strategies to prevent them through a scoping review. Data were gathered through a scoping review of PubMed, Emba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, participants also discussed lack of participatory management from leadership which demonstrates lack of teamwork on the part of leadership. Lack of team cohesion can lead to medical errors which are detrimental to patient care and outcomes [ 17 ]. Leadership has a key function in promoting teamwork as their contributions can have a direct impact on organizational culture [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, participants also discussed lack of participatory management from leadership which demonstrates lack of teamwork on the part of leadership. Lack of team cohesion can lead to medical errors which are detrimental to patient care and outcomes [ 17 ]. Leadership has a key function in promoting teamwork as their contributions can have a direct impact on organizational culture [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to their data, pressure ulcers were the most common measurable medical error, followed by postoperative infections and then postlaminectomy syndrome [6] Aghighi et al reported that 2 main categories of factors were identified as influential in error recurrence: human factors (fatigue, stress, inadequate knowledge) and environmental and organizational factors (ineffective management, distractions, poor teamwork). The six effective strategies for preventing error recurrence included the use of electronic systems, attention to human behaviors, proper workplace management, workplace culture, training, and teamwork [7].…”
Section: Our Missionmentioning
confidence: 99%
“…Nurses, pharmacists, technicians, caregivers and patients themselves are all important participants to discover and reduce ME. [41][42][43] Future studies could be broader interviews, questionnaire surveys (eg, Safety Attitudes Questionnaire) and incident reporting system data follow-ups with safety interventions to evaluate the changes.…”
Section: Subsequent Management Of Mementioning
confidence: 99%